Surveillance of Influenza B Virus Strains Circulating in Malaysia (2002—2006) - T.R.T., Rashid; Z., Saat; M.A., Yusof; S.J., Berendam; F. Md., Kassim; K.A., Othman; S.K., Lau; N.S., Khairullah; S., Lihan (Elsevier Inc., 2008)
Background: The Virology Unit, Institute for Medical Research (IMR), Kuala Lumpur has been designated as the National Influenza Centre since 1968, carrying out influenza surveillance activities for the Ministry of Health Malaysia. These activities are important for preparation of epidemics and pandemics. In the past decade, several outbreaks of influenza B have been reported in this country. Thus, the aims of this study are to evaluate the incidence and to identify the circulating viral strain of influenza type B in Malaysia. Methods: All respiratory specimens received from several sentinel sites from patients presenting with influenza-like illness (ILI) were included in this study. The virus was detected by culture method using Madin Darby Canine Kidney (MDCK) cells with combination of Immunofluorescence (IF) and haemagglutination inhibition (HAI) techniques. Results: From 2002 to 2006 the National Influenza Centre, IMR received a total of 5,463 specimens from patients presenting with ILI. Of these, 220 (4.0%) were found to be positive for Influenza B virus and further analysis showed that there were four major strains circulating in Malaysia during the five years study period. The predominant strain in 2002 was B/Hong Kong/330/2001-like virus, B/Sichuan/379/99-like virus in 2003, B/Shanghai/361/2002- like virus in 2004, B/Hong Kong/330/2001-like virus in 2005 and B/Malaysia/2506/2004-like virus in 2006. Conclusion: The surveillance activities are not only important as an early warning for outbreak preparedness but also important in detecting new strains that can be used in the annual vaccine formulation.